2011
DOI: 10.3892/ol.2011.437
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ERα36 in gastric cancer samples and their matched normal tissues

Abstract: Abstract. Estrogen receptor α36 (ERα36) is believed to mediate membrane-initiated effects of estrogen signaling, and promote cell growth and resistance to tamoxifen treatment. However, few studies are available regarding ERα36 expression in gastric cancer. In the present study, we evaluated the expression of ERα36, as well as estrogen receptor α66 (ERα66), in gastric cancer and its correlation with clinicopathological parameters. Real-time polymerase chain reaction (PCR) was applied to detect the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, the ERα36 mRNA was also found in various healthy estrogen-sensitive tissues such as the mammary gland, the uterus, the bone and cartilage tissues, renal tubules, the stomach, etc. [31][32][33][34][35][36]. This suggested that this variant could participate in mediating the physiological effects of estrogens.…”
Section: Consequences Of Erα36 Expression In Non-cancerous Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the ERα36 mRNA was also found in various healthy estrogen-sensitive tissues such as the mammary gland, the uterus, the bone and cartilage tissues, renal tubules, the stomach, etc. [31][32][33][34][35][36]. This suggested that this variant could participate in mediating the physiological effects of estrogens.…”
Section: Consequences Of Erα36 Expression In Non-cancerous Cellsmentioning
confidence: 96%
“…Although the expression of ERα36 is very high in several gastric cancer cell lines (SGC-7901, AGS, BGC-923, and MKN-45), two independent clinical studies regarding the expression of ERα36 in gastric cancer produced conflicting results. Indeed, in these two studies, the amount of ERα36 mRNA in cancer samples is alternately higher [72] or lower [33] than in normal tissue and ERα36 expression was not significantly associated with gender, age, grading, size of the tumor, or lymph node metastasis. However, ERα-36 expression positively correlated with Cyclin D1 and GRP94, two downstream effectors of ERα36-mediated non genomic estrogen signaling that could help to explain ERα36 function during gastric carcinogenesis [72,73].…”
Section: Gastric Cancermentioning
confidence: 99%
“…This is also supported by our evidence that the estrogen receptor variant ERα36 was detected specifically in the female LGKO with liver tumors. Fourth, although it is not currently clear about how ERα36 mechanistically causes or regulates hepatic tumorigenesis, overexpression of ERα36 has been linked to carcinogenesis in other systems such as breast cancer and gastric cancer . Therefore, by combining the information from the literature with our results, we propose a specific link of long‐term ER stress with HCA in females.…”
Section: Discussionmentioning
confidence: 65%
“…Overexpression of coactivators, for example coactivator-associated arginine methyltransferase 1, may also increase the expression of ERα target genes involved in breast tumor cell differentiation and proliferation ( 26 ), including breast cancer (BRCA) 1 and BRCA2 genes ( 27 ). In addition, reduction of ERα spliced variant 46 (46 kDa) and 36 (36 kDa) mRNA levels have been observed in colon tumors ( 28 ) and overexpression of ERα36 has been observed in gastric ( 29 ) and endometrial cancers ( 30 ).…”
Section: Er Proteins and Tumor Diseasesmentioning
confidence: 99%